Neural Correlates of Intentional Communication - Noordzij, Matthijs L.; Newman-Norlund, Sarah E.; De Ruiter, Jan P.; Hagoort, Peter; Levinson, Stephen C.; Toni, Ivan (Frontiers in Neuroscience, 2010)
We know a great deal about the neurophysiological mechanisms supporting instrumental actions, i.e. actions designed to alter the physical state of the environment. In contrast, little is known about our ability to select communicative actions, i.e. actions directly designed to modify the mental state of another agent. We have recently provided novel empirical evidence for a mechanism in which a communicator selects his actions on the basis of a prediction of the communicative intentions that an addressee is most likely to attribute to those actions. The main novelty of those finding was that this prediction of intention recognition is cerebrally implemented within the intention recognition system of the communicator, is modulated by the ambiguity in meaning of the communicative acts, and not by their sensorimotor complexity. The characteristics of this predictive mechanism support the notion that human communicative abilities are distinct from both sensorimotor and linguistic processes.